Gender Characteristics and Comparisons in the Emotional Reception of Standard and Aesthetically Integrated Subtitles in a Fantasy-Thriller Context - Mevel, Pierre-Alexis; Leveridge, Francesca; Tsikandilakis, Myron (Journal of Audiovisual Translation, 2025)
In this article, we test the findings by Leveridge and colleagues (2024) regarding the reception of aesthetically integrated subtitles (AIS), and most critically, we explore the role of gender in these outcomes. We explore psychophysiological (skin conductance and heart rate) and self-report responses (questionnaires) among three different subtitle deliveries (no subtitles, standard subtitles, and aesthetically integrated), and between male and female participants in a series of clips from the Russian thriller-horror film Night Watch (Bekmambetov, 2004). This research involves an entire array of film clips, including AIS from Night Watch. We use null-hypothesis-significance-testing (NHST) and Bayesian analyses to explore the claim that AIS enhance psychophysiological arousal and viewing experience quality compared to standard subtitles (STS) and investigate the gender characteristics and differences in the reported outcomes. We provide a replication of previous findings. Critically, we show that female participants exhibited higher arousal for AIS, also separately for all subtitle types, which was not reflected in significant between-gender differences for self-reports for intensity and arousal. In another novel section of this research, we show that AIS increased interest in film genres for both genders, suggesting their significant potential for future audiovisual translation practices. Lay summary In this article, we look at how different types of film subtitles affect viewers, focusing on whether gender plays a role in these effects. We tested three types of subtitles: no subtitles, regular subtitles displayed in white letters at the bottom of the screen, and a special type called aesthetically integrated subtitles (AIS), which are designed to blend more seamlessly with the movie through the use of visual effects, colour, or font. Using clips from the Russian thriller-horror film Night Watch (Bekmambetov, 2006), we measured people's physical responses, like heart rate and skin conductance, as well as their feelings about the experience through the use of questionnaires. Our findings build on previous research and show that AIS can enhance the viewing experience. Interestingly, we found that women showed higher physical arousal (like increased heart rate) when watching movies with subtitles, especially AIS, but this did not translate into significant differences in how intense or engaging they said the clips felt compared to men. We also discovered that AIS made both men and women more interested in different film genres, suggesting that these subtitles could be useful in future audiovisual translations and productions.